Analysis Of Nurse Obedience in The Standard Precautions of Healthcare Associated Infections (HAIs) - Dachirin, Wachid; Kuswardinah, Asih; Handayani, Oktia Woro Kasmini (Universitas Negeri Semarang, 2020)
The prevalence of healthcare associated infections (HAIs) is increasing which caused by higher morbidity and mortality rates. Efforts are made to prevent and control the transmission of disease from patients to health care workers or vice versa is the application of Standard Precautions. This study determined the analysis of standard precautions obedience to prevent HAIs at Nahdlotul Ulama (NU) Demak hospital. This research was a quantitative with cross sectional design. The population were nurses at NU Demak hospital, and based on purposive sampling technique, there were 67 respondents. Data analysis uses Pearson Product Momment and Linear Regression. The results of this study indicate that partially influence of independent variables on standard precautions to prevent HAIs, namely in education (p = 0,000), knowledge (p = 0,000), training (p = 0,000), facility (p = 0,000), support get (p = 0,000) and supervision (p = 0,000). These results indicate that all variables have a positive effect on nurses obedience with standard precautions preventing HAIs at NU Demak hospital. The effect simultaneously gets a p value of 0,000, which means that there is a simultaneous influence of the independent variable on nurses obedience in standard precautions to prevent HAIs.